2004
DOI: 10.1128/iai.72.5.3038-3041.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Extra Cytoplasmic Function Sigma Factor σ E Is Essential for Mycobacterium tuberculosis Virulence in Mice

Abstract: The virulence of a Mycobacterium tuberculosis H37Rv sigE mutant was studied in immunodeficient and immunocompetent mice. The mutant was strongly attenuated in both animal models and induced formation of granulomas with different characteristics than those induced by the wild-type strain.During infection, bacteria often face different environments which result from the site in which the pathogen resides as well as activation of the host's immune response. To be successful, a pathogen must be able to adapt quick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 15 publications
3
71
0
Order By: Relevance
“…SigE, however, was reported to be required for survival of H37Rv in macrophages (Manganelli et al, 2001). In addition, a sigE mutant persisted less effectively than the H37Rv parent strain in the lungs, spleen and liver of BALB/c mice, and mice infected with the mutant survived longer than those infected with the parent strain (Manganelli et al, 2004). Interestingly, while C3H/HeJ mice infected with a sigE mutant of the CDC1551 strain also survived longer than those infected with the parent strain, the mutant was not impaired for lung persistence (Ando et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…SigE, however, was reported to be required for survival of H37Rv in macrophages (Manganelli et al, 2001). In addition, a sigE mutant persisted less effectively than the H37Rv parent strain in the lungs, spleen and liver of BALB/c mice, and mice infected with the mutant survived longer than those infected with the parent strain (Manganelli et al, 2004). Interestingly, while C3H/HeJ mice infected with a sigE mutant of the CDC1551 strain also survived longer than those infected with the parent strain, the mutant was not impaired for lung persistence (Ando et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of SigE-regulated genes (Manganelli et al, 2004) was evaluated in SDS-treated and control cultures of H37Rv and Rv-D981, using array analyses or real-time PCR (qPCR). For each gene, results show fold induction under SDS compared to the control sample for the same strain.…”
Section: Global Patterns Of Gene Expression In Rv-d981mentioning
confidence: 99%
“…Similar to rpoE of Escherichia coli (Mecsas et al, 1993;Tam & Missiakas, 2005), M. tuberculosis sigE may, therefore, be induced by envelope stress, but the mechanisms involved have not been determined. Deletion of sigE in mycobacteria is associated with reduced resistance to SDS and oxidative stress, decreased growth in macrophages (Manganelli et al, 2001;Wu et al, 1997), and reduced growth in mice (Ando et al, 2003;Manganelli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This capacity to persist in the host, despite the dynamic alterations effected by the host immune response, testifies to an evolved capacity of the organism to regulate its genetic expression to the conditions encountered during infection. Indeed, a number of studies have demonstrated that disruption of M. tuberculosis regulatory elements, such as sigma factors, results in reduced virulence in experimental models (21,28,30).The determination of genomic sequences for a number of nonpathogenic mycobacteria has revealed that homologues of many genes, including regulatory elements, are often present in organisms that are not virulent to humans. For instance, comparative analysis has demonstrated conservation of biochemical pathways and a secretory system important for full virulence of M. tuberculosis (7,10).…”
mentioning
confidence: 99%
“…This capacity to persist in the host, despite the dynamic alterations effected by the host immune response, testifies to an evolved capacity of the organism to regulate its genetic expression to the conditions encountered during infection. Indeed, a number of studies have demonstrated that disruption of M. tuberculosis regulatory elements, such as sigma factors, results in reduced virulence in experimental models (21,28,30).…”
mentioning
confidence: 99%